The stellar orbit distribution in present-day galaxies inferred from the CALIFA survey - Zhu, Ling; Grand, Robert J. J. (Arxiv, 2018)
Galaxy formation entails the hierarchical assembly of mass, along with the condensation of baryons and the ensuing, self-regulating star formation. The stars form a collisionless system whose orbit distribution retains dynamical memory that can constrain a galaxy's formation history. The ordered-rotation dominated orbits with near maximum circularity $λ_z \simeq1$ and the random-motion dominated orbits with low circularity $λ_z \simeq0$ are called kinematically cold and kinematically hot, respectively. The fraction of stars on `cold' orbits, compared to the fraction of stars on `hot' orbits, speaks directly to the quiescence or violence of the galaxies' formation histories. Here we present such orbit distributions, derived from stellar kinematic maps via orbit-based modelling for a well defined, large sample of 300 nearby galaxies. The sample, drawn from the CALIFA survey, includes the main morphological galaxy types and spans the total stellar mass range from $10^{8.7}$ to $10^{11.9}$ solar masses. Our analysis derives the orbit-circularity distribution as a function of galaxy mass,